Evaluation of a newly introduced tonsillectomy operation record for the analysis of regional post-tonsillectomy bleed data: a quality improvement project at the London North West Healthcare NHS Trust. Issue 2 (26th October 2017) - Lechner, Matt; Chandrasekharan, Deepak; Vithlani, Rohan; Sutton, Liam; Grandidge, Carly; Elmiyeh, Behrad
Abstract : The primary objective of this audit and quality improvement project was to retrospectively analyse regional post-tonsillectomy haemorrhage data as per national recommendations. However, this process highlighted the need for high-quality routinely collected data; something that was not always available via retrospective audit and thus does not enable formal aetiological factor analyses. We therefore created further secondary objectives to facilitate our primary audit objective. These secondary objectives were (1) to introduce a standardised tonsillectomy operation proforma to improve completeness and quality of routinely collected data and (2) to evaluate and validate proforma use and usefulness in improving using routine data collection to help with a repeated audit of post-tonsillectomy haemorrhages with the eventual aim to help improve operative outcomes by identifying potential associated factors. The retrospective audit component, the prospective audit and the quality improvement component were all carried out at the Northwick Park Hospital and Central Middlesex Hospital (London North West Healthcare NHS Trust). First, 642 tonsillectomy records (2012–2014) were retrospectively reviewed. Free-text operative documentation and, where possible, potential factors associated with post-tonsillectomy haemorrhages were analysed. In addition, completeness of data available before and after the introduction of (A) a new paper-based and (B) electronic surgical record proforma was reviewed (2014–2015). Over a 2-year period, 62 of the 642 (9.7%) audited tonsillectomy patients had a post-tonsillectomy haemorrhage, and 19 of these (2.9%) had to return to theatre for surgical arrest of the haemorrhage. Bipolar diathermy was the most commonly used technique. During this period, data available from routine operative documentation in the surgical operation notes were variable and thus did not allow identification of potential factors associated with post-tonsillectomy haemorrhage. The completeness and quality of data significantly improved after the introduction of a standardised paper-based proforma with sections for required details based on known risk factors for post-tonsillectomy haemorrhage and required operative details. Quality and completeness of data was further improved after the introduction of an electronic version.This electronic proforma will allow prospective spiral auditing results, early identification of raised bleeding rate, and provide individual surgeon audit results.